TRANGRESSING AFFECTIVE INTERSECTIONS AND FLUID IDENTITIES: A LIMINAL STUDY OF LABURNUM FOR MY HEAD - Pillai, Rashmi S (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Women’s Narratives from the Eastern Himalaya, when analysed critically, portray that there is a constant spatial transition of identity, and belongingness. Social structures normally undergo transformations, which are usually short term, but can make human beings willingly give up their previous identities and eventually acquire homogenised states which are new, ready-made, and normal. This paper attempts to analyse women characters who come across daily instances of liminal fluidity which manipulates affectivity in spite of fluid conjunctures. The paper also analyses how there is reconciliation between spaces and identities, in the select narratives from the anthology of stories, Laburnum for my Head, by Temsula Ao.